(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To describe a radiological approach for evaluation of bony anatomical variants of paranasal sinuses prior to FESS. Materials and Methods: Patients referred from the Dept of ENT with the diagnosis of chronic sinusitis but who had failed medical treatment and are now candidates for FESS were included. Their CT was conducted to ascertain the bony variations that could complicate FESS. These patients later underwent surgery. The preop radiological findings were compared to operative findings and the results were recorded and late malted. Results: The results of our study showed that CBCT is an absolute pre requisite before FESS. Conclusion: Study concludes that many catastrophic per operative complications can be avoided by conducting pre operative CBCT.